WORKFORCE SIZING AND SCHEDULING FOR A SERVICE CONTRACTOR USING INTEGER PROGRAMMING - Conradie, D.G.; Joubert, J.W. (South African journal of industrial engineering, 2012)
ENGLISH ABSTRACT: Operations Research is perceived to be on the verge of demise as a decision support tool in industry. However, this is not true, since the relevancy and interdisciplinary nature of Operations Research makes it an indispensable part of operations management. What should rather be asked is how Operations Research is introduced to undergraduate industrial engineering students. This paper reports on one of the optimisation initiatives undertaken for a service contractor using integer programming as part of a semester project. Although the model addresses specific business issues related to the contractor, it can easily be generalised for other applications. AFRIKAANSE OPSOMMING: Operasionele Navorsing word geag as ’n kwynende besluitnemingsinstrument in die nywerheid. Dit is egter onwaar, aangesien die toepaslikheid en interdissiplinêre karakter van Operasionele Navorsing dit ‘n onmisbare rol laat speel in operasionele bestuur. Die vraag wat eerder gevra moet word is hoe Operasionele Navorsing aan voorgraadse bedryfsingenieurswesestudente aangebied word. Hierdie artikel doen verslag oor een van die optimerings-inisiatiewe wat as deel van ‘n semesterprojek vir ‘n diensverskaffer uitgevoer is, en maak van heeltal-programmering gebruik. Alhoewel die model kontrakteur-spesifieke besigheidsreëls aanspreek, kan dit maklik veralgemeen word vir wyer toepassing.